The Role of Social Interaction and Attitude Toward Using in Online Learning during the Covid 19 Pandemic: An SDL Theory Perspective - Andi - Setiawan; Saptianing - Saptianing; Riyadi - Riyadi (Admisi dan Bisnis, 2022)
The Covid-19 pandemic has created a situation that requires students to accept Online Learning as a consequence. Universities must turn barriers to online learning into an advantage for students. Our study draws on established Service-Dominant Logic (SDL) theory and literature to examine holistically how the value of online learning is perceived and co-created by two key stakeholders, namely professional service providers (Universities) and their clients in online learning (students). Therefore, this study aims to develop and test a conceptual model of the factors that influence student adoption of online learning systems, especially those built from easy-to-use variables. pleasure, social interaction, and user behavior. The data for this study were obtained from online questionnaire responses (n=179) and then analyzed using structural equation modeling. The results of this study confirm that the expansion of the SDL provides a useful theoretical model to help understand and explain the acceptance and use of technology (UTAUT) in online learning models. The results of this study also show that UTAUT is a factor that positively affects the variables of pleasure, social interaction, and attitude toward using.